Biofiltration of trimethylamine in biotrickling filter inoculated with Aminobacter aminovorans - Alberto Aguirre; Pamela Bernal; Daniela Maureira; Nicolás Ramos; Javier Vásquez; Homero Urrutia; Juan Carlos Gentina; Germán Aroca (Electronic Journal of Biotechnology, 2018)
Background: Trimethylamine (TMA) is the main responsible for the odor associated with rotting fish and other annoying odors generated in many industrial activities. Biofiltration has proved to be efficient for treating odorous gaseous emissions. The main objective of this work was to determine the removal capacity of TMA of a biotrickling filter inoculated with Aminobacter aminovorans and to evaluate the effect of H2S on its performance. Results: The maximum specific growth rate of A. aminovorans in a liquid culture was 0.15 h-1, with a TMA to biomass yield of 0.10 (g g-1) and a specific consumption rate of 0.062 g·g-1·h-1. The initial specific consumption rate of TMA was highly influenced by the presence of H2S in liquid culture at concentrations of 20 and 69 ppm in heading space of the flasks. A BTF inoculated with A. aminovorans showed removal efficiencies higher than 98% in a range of loading rate of 0.2 to 8 g·m-3·h-1 at empty bed residence time (EBRT) of 85 and 180 s. No effect on the elimination capacity and efficiency was detected when H2S was added at 20 and 50 ppm to the inlet gaseous emission, though the fraction of A. aminovorans measured by qPCR in the biofilm decreased. Conclusions: A biotrickling filter inoculated with A. aminovorans can remove efficiently the TMA in a gaseous stream. The elimination capacity of TMA can be negatively affected by H2S, but its effect is not notorious when it is forming part of a biofilm, due to its high specific consumption rate of TMA.How to cite: Aguirre A, Bernal P, Maureira D, et al. Biofiltration of trimethylamine in biotrickling filter inoculated with Aminobacter aminovorans. Electron J Biotechnol 2018;33. https://doi.org/10.1016/j.ejbt.2018.04.004. Keywords: Aminobacter aminovorans, Biofiltration, Biotrickling filter, Deodorization, Gaseous emissions, Hydrogen sulfide, Odor nuisance, Odorous emissions, Rotting fish, Trimethylamine, Volatile amines